Community-based intervention in mosquito control strategy: A systematic review - Yulfi, Hemma; Panggabean, Merina; Darlan, Dewi M.; Siregar, Irma SS.; Rozi, Muhammad F. (Narra J, 2025)
As part of the World Health Organization’s One Health Initiative, vector-borne disease control requires multidisciplinary and community involvement. This review examined community-based mosquito control intervention methods, their efficacy, and limitations. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guideline, data were extracted from four medical databases: PubMed, Clinical Key, ProQuest, and ScienceDirect, covering the period from 2014 to 2023. The search used the keywords "community intervention," "vector control," and "mosquito." Filters were applied for full text, primary sources, scholarly journals, and publications within the last ten years (2014–2023). Studies without community intervention components were excluded. The initial search retrieved 1,035 articles, and 32 full-text articles were selected and assessed for eligibility, with 15 papers included in the final analysis. The included studies focused on arbovirus or malaria vectors and used randomized controlled trials (RCTs), pre- and post-intervention surveys, community-based implementation surveys, or qualitative research designs. Commonly applied interventions included community-driven vector population control and community education. Overall, the studies reported improvements in outcome measures such as entomological indices, community knowledge and practices, costs, and disease incidence or prevalence. However, some studies reported challenges with community perception and acceptance. In conclusion, this review consistently demonstrated a positive impact of community interventions on managing mosquito control.